2002
DOI: 10.1046/j.1365-201x.2002.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of controlled hypoxia and radical scavenging agents on erythropoietin and malondialdehyde concentrations in humans

Abstract: Taken together, our in-vivo results do not support a gross modulatory effect of a short-term treatment with radical scavenging agents on EPO-production during or after hypoxia in humans, as derived from the detected changes of MDA-concentrations in peripheral plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
(45 reference statements)
2
19
0
1
Order By: Relevance
“…10 The end products of the reactions between ROS and polyunsaturated fatty acids are hydroperoxides, and malondialdehyde is one of the major aldehydes produced by the breakdown of such hydroperoxides. The hypoxia-reoxygenation cycles in OSAS were suggested to cause increases in malondialdehyde levels, which was also confirmed by the studies that showed increased malondialdehyde levels following hypoxemia in healthy controls, 40 or hyperoxic reoxygenation in surgical subjects. 41 Our results also confirm these findings.…”
Section: Discussionsupporting
confidence: 66%
“…10 The end products of the reactions between ROS and polyunsaturated fatty acids are hydroperoxides, and malondialdehyde is one of the major aldehydes produced by the breakdown of such hydroperoxides. The hypoxia-reoxygenation cycles in OSAS were suggested to cause increases in malondialdehyde levels, which was also confirmed by the studies that showed increased malondialdehyde levels following hypoxemia in healthy controls, 40 or hyperoxic reoxygenation in surgical subjects. 41 Our results also confirm these findings.…”
Section: Discussionsupporting
confidence: 66%
“…The order of magnitude of the increase of Epo concentrations in humans under i.v. AII administration is very similar to that of hypoxia (exposure to 13% O 2 or altitude levels of about 4000 m) [5,23,24].…”
Section: Discussionmentioning
confidence: 70%
“…Freudenthaler S et al increased concentrations of endogenous angiotensin II and PRA and decreased GFR and RPF significantly, with no concomitant alteration of Epo regulation in humans [17]. Reversely, the majority of the following examples concern [20]. Gargano G et al improved epoetin-α or r-HuEPO SC administration by sodium ferrous gluconate administered IV along [21], [22].…”
Section: Discussionmentioning
confidence: 99%